2006
DOI: 10.1007/s10529-006-9048-0
|View full text |Cite
|
Sign up to set email alerts
|

New Enzyme-based Process Direction to Prevent Wool Shrinking without Substantial Tensile Strength Loss

Abstract: In this paper a new enzymatic process direction is described for obtaining machine washable wool with acceptable quality. In general, application of protease enzyme technology in wool processing results in considerable loss of tensile strength by diffusion of the enzyme into the interior of wool fibers. To overcome this disadvantage enzymatic activity has been more targeted to the outer surface of the scales by improving the susceptibility of the outer surface scale protein for proteolytic degradation. This ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…For the wool fabric treated with protease alone, there was no remarkable change in the wettability, indicating that no obvious hydrolytic cleavage of the bound lipids had occurred in the cuticle membrane of the wool. In other words, protease molecules themselves did not have an effect on the hydrophobic aliphatic esters on the wool surface; they preferably penetrated into the fiber cortex, resulting in moderate removal of the interior peptide and protein segments . Therefore, the wettability of the protease‐treated wool was not as satisfactory as that after MPH treatment.…”
Section: Resultsmentioning
confidence: 99%
“…For the wool fabric treated with protease alone, there was no remarkable change in the wettability, indicating that no obvious hydrolytic cleavage of the bound lipids had occurred in the cuticle membrane of the wool. In other words, protease molecules themselves did not have an effect on the hydrophobic aliphatic esters on the wool surface; they preferably penetrated into the fiber cortex, resulting in moderate removal of the interior peptide and protein segments . Therefore, the wettability of the protease‐treated wool was not as satisfactory as that after MPH treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these processes have been tested on industrial process scale (Shen et al 2007). Pretreatment of wool fibres with hydrogen peroxide, at alkaline pH in the presence of high concentrations of salts, also targets enzymatic activity to the outer surface of wool, by improving the susceptibility of the cuticle to proteolytic degradation (Lenting et al 2006).…”
Section: Enzymatic Treatment Of Woolmentioning
confidence: 99%
“…Considerable researches have shown that protease treatment can improve the dyeability and shrink resist of wool . However, the outer surface of the scales are highly cross‐linked and in practice hardly substrate for proteolytic enzymes . To make enzymatic action effective, the outer scale protein still has to be modified prior to enzymatic incubation.…”
Section: Introductionmentioning
confidence: 99%